Comparing the nutritional status of vegetarians and non-vegetarians from a Buddhist organisation in Kuala Lumpur, Malaysia - Gan, Wan Ying; Boo, Shirley; Seik, Mei Yee; Khoo, Hock Eng (Nutrition Society of Malaysia, 2018)
Introduction: A vegetarian diet is generally considered as healthy for preventing metabolic-related diseases. There is lack of studies in Malaysia comparing the nutritional status of vegetarians and non-vegetarians. This cross-sectional study aims to compare body weight status, dietary intake and blood pressure level between these two groups. Methods: A total of 131 vegetarians and 135 non-vegetarians were recruited using convenience sampling from a Buddhist organisation in Kuala Lumpur. Body weight, height, waist circumference, percentage of body fat, and blood pressure measurements were taken, while dietary intake was assessed using a 2-day 24-hour dietary recall. Results: More vegetarians were underweight than non-vegetarians (31.3% vs 15.6%), while prevalence of overweight and obesity was higher among the non-vegetarians (23.7% vs 9.9%). A higher proportion of non-vegetarians (34.1%) had an unhealthy range of body fat percentage and significantly higher risk of abdominal obesity (24.4%) than the vegetarians (19.1% body fat; 13.7% abdominal obesity). Mean intakes for protein and fat were significantly lower among the vegetarians, while no significant differences were observed in the mean intake for energy and carbohydrate. Vegetarians had significantly higher intakes of vitamins C, D and E, calcium, potassium and folate, while vitamin B12 intake was significantly higher in the non-vegetarians. More non-vegetarians presented with unhealthy blood pressure status. Conclusion: Vegetarians in this study generally showed healthier dietary intake and lower body fatness than the non-vegetarians. Studies are suggested to be undertaken on a bigger sample size of vegetarians to confirm these findings.